Anti-corrosion and fireproof integrated coating and preparation method thereof

By adopting a multi-layer structure in the building coating, including nano-silicon coating, sealing layer, sealing coating layer, reactive primer layer and polyurea topcoat layer, the problems of insufficient adhesion and poor durability between traditional coating layers are solved, and higher adhesion, lower water absorption, better durability and fire resistance are achieved.

CN119875407AActive Publication Date: 2025-04-25CHINA STATE CONSTR INT ENG CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510370501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

Traditional anti-corrosion and fire-resistant coatings in buildings have problems of insufficient adhesion between layers and poor durability, especially peeling and water vapor penetration caused by differences in thermal expansion coefficients.

Method used

The anti-corrosion and fire-resistant integrated coating with a multi-layer structure, including nano-silicon coating, sealing layer, sealing coating layer, reactive primer layer and polyurea topcoat layer, is used to form a dense interface layer through the synergistic effect of silane coupling agent and nano-silicon sol, and nano-silica and graphene nanosheets are introduced to improve the adhesion and durability of the coating.

Benefits of technology

The adhesion between the coating and the concrete base is significantly improved, the water absorption rate is reduced, the durability is improved, the fire resistance limit is extended to 1.5 hours, and the light retention rate remains above 90% in the ultraviolet aging test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-corrosion and fireproof integrated coating and a preparation method thereof, and relates to the technical field of building coatings, and the anti-corrosion and fireproof integrated coating comprises a nanometer silicon coating on the surface of a concrete base layer; a sealing layer, a closed coating layer, a reaction type active primer layer and a polyurea finishing coat layer are sequentially arranged on the surface, far away from the concrete base layer, of the nano silicon coating; the nano silicon coating is prepared from the following raw materials in parts by weight: 70-90 parts of nano silicon sol; 1-2 parts of a silane coupling agent; 15 to 20 parts of deionized water; and 0.1 to 0.5 part of a dispersant. In the nano silicon coating, the silane coupling agent and the nano silicon sol are added to form a compact inorganic-organic hybrid interface layer, so that the adhesive force between the coating and a concrete base layer is greater than or equal to 5MPa, the water absorption rate is less than or equal to 0.5%, and the adhesive force is improved by more than 50% compared with that of the traditional epoxy primer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building coatings, in particular to an anti-corrosion and fire-proof integrated coating and a preparation method thereof. Background Art

[0002] Traditional building anticorrosion and fireproof coatings mostly adopt single-layer or double-layer structures (such as primer + topcoat), which have the following technical defects: due to the difference in thermal expansion coefficients, the concrete base and the coating are prone to peeling, resulting in anticorrosion failure. Conventional sealing layer fillers (such as talcum powder and calcium carbonate) have high porosity and cannot effectively block the penetration of water vapor and corrosive media. The salt spray test life is generally less than 800 hours; the temperature and humidity control in the multi-layer coating process is not accurate, which is prone to defects such as bubbles and sagging, affecting the density of the coating. Summary of the invention

[0003] In view of the problems existing in the existing anti-corrosion and fire-proof integrated coating and preparation method thereof, the present invention is proposed.

[0004] Therefore, the problem to be solved by the present invention is that the interlayer adhesion of the coating is insufficient and the durability is poor.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: In a first aspect, an embodiment of the present invention provides an anti-corrosion and fire-proof integrated coating, comprising a concrete base layer, and also comprising a nano-silicon coating on the surface of the concrete base layer; A sealing layer, a sealing coating layer, a reactive active primer layer, and a polyurea topcoat layer are sequentially arranged on the surface of the nano-silicon coating away from the concrete base layer; The nano silicon coating is made of the following raw materials in parts by weight: Nano-silica sol: 70-90 parts; silane coupling agent: 1-2 parts; deionized water: 15-20 parts; dispersant: 0.1-0.5 parts.

[0006] As a preferred solution of the anti-corrosion and fire-proof integrated coating of the present invention, the sealing layer is made of the following raw materials in parts by weight: Styrene acrylic emulsion: 55-90 parts; calcium carbonate: 30-40 parts; titanium dioxide: 2-5 parts; talcum powder: 10-15 parts; nano silicon dioxide: 5-10 parts; leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part.

[0007] As a preferred solution of the anti-corrosion and fire-proof integrated coating of the present invention, the closed coating layer is made of the following raw materials in parts by weight: Polyurethane: 35 parts; Water: 55-60 parts; Pigment: 9 parts; Film-forming aid: 8 parts; Thickener: 0.7 parts; Bactericide: 0.3 parts; PH regulator: 0.1 parts; Defoamer: 0.2 parts; Bridging agent: 1 part.

[0008] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the reactive active primer layer is made of the following raw materials in weight fractions: Polyaspartic acid ester resin: 50 parts; water: 30 parts; propylene glycol methyl ether: 10 parts; active diluent: 10 parts; curing agent: 20 parts; leveling agent: 1 part.

[0009] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the polyurea topcoat layer is made of the following raw materials in parts by weight: Polyaspartic acid ester resin: 50-70 parts; aliphatic isocyanate: 30-40 parts; active diluent: 20-30 parts; ultraviolet absorption aid: 0.5-5 parts; film-forming aid: 10 parts; silicone aid: 5 parts; graphene nanosheets: 0.1-0.5 parts.

[0010] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the preparation method of the sealing layer comprises: Stir styrene acrylic emulsion, leveling agent, wetting agent, film-forming aid and deionized water at 80°C for 30-45 minutes at a stirring speed of 250-300 r / min; Then add calcium carbonate, titanium dioxide, talcum powder, and nano silicon dioxide in stages, and adjust the stirring speed to 500-600r / min; Add thickener and continue stirring for 10-15 minutes. When the stirring temperature rises to 90°C and the viscosity reaches 80-90KU / 25°C, stop stirring. Obtain a closed layer.

[0011] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the method for preparing the closed coating layer comprises: Polyurethane, water, pigment, film-forming aid, thickener, bactericide, pH regulator, defoamer, and bridging agent are mixed in a high-speed disperser at 40-50°C, with a stirring speed of 1000-1200 r / min, for 20-40 minutes, and the viscosity reaches 150±20KU / 25°C, to obtain a uniform closed coating dispersion with a fineness of less than 50μm; Obtain a closed coating layer.

[0012] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the preparation method of the reactive active primer layer comprises: Disperse polyaspartic acid ester resin, water, propylene glycol methyl ether, active diluent, curing agent and leveling agent at 40-50°C and stirring speed of 800-1000r / min for 30-45min, add thickener and continue stirring for 10-15min, stop stirring when the viscosity reaches 5-10Ku; A reactive active primer layer is obtained.

[0013] As a preferred embodiment of the anti-corrosion and fire-proof integrated coating of the present invention, the preparation method of the polyurea topcoat layer comprises: Add the active diluent to the high-speed disperser, slowly add the graphene nanosheets, start the high-speed disperser at the same time, set the stirring speed to 1000-2000r / min, and continue dispersing for 30-60min to form a pre-dispersed mixed solution; Transfer the pre-dispersed mixed liquid to the container of a vacuum mixer, then add the polyaspartic acid ester resin and set the stirring speed to 300-500r / min; During the stirring process, slowly add the UV absorbing agent, film-forming agent and silicone agent, and set the stirring time to 10-15 minutes; Then add aliphatic isocyanate, set the stirring speed to 800-1200r / min, and stir for 10-15min; Add thickener and continue stirring for 10-15 minutes. When the viscosity reaches 70-90KU / 25℃, stop stirring. A polyurea topcoat layer was obtained.

[0014] In a second aspect, an embodiment of the present invention further provides a method for preparing an anti-corrosion and fireproof integrated coating, comprising the above-mentioned anti-corrosion and fireproof integrated coating, and the method for preparing the anti-corrosion and fireproof integrated coating further comprises the following steps: Clean the surface of the concrete base away from the wall: Apply a layer of nano silicon coating on the surface of the concrete base; A sealing layer is provided on the surface of the nano-silicon coating: a latex paint of the sealing layer is applied on the surface of the nano-silicon coating through a coating roller, and the speed of the coating roller is controlled at 20-30 N / MIN; Set a sealed coating layer on the surface of the sealing layer: use a coating roller to apply it on the surface of the sealing layer, and the speed of the coating roller is 20-25N / MIN; A reactive active primer layer is provided on the surface of the sealed coating layer: a reactive active primer layer is applied on the surface of the sealed coating layer through a coating roller, and the rotation speed of the coating roller is controlled at 20 to 30 N / MIN; A polyurea topcoat layer is provided on the surface of the reactive active primer layer: the polyurea topcoat layer is applied on the surface of the reactive active primer layer through a coating roller, and the rotation speed of the coating roller is controlled at 20 to 30 N / MIN; The coated coating is reacted at a temperature of 70-85°C and a humidity of 70-85RH% for 16-24 hours, and then at a temperature of 30-35°C and a humidity of 70-85RH% for 12-18 hours to form an integrated coating.

[0015] The beneficial effects of the present invention are: In the nano-silicon coating, a dense inorganic-organic hybrid interface layer is formed by adding silane coupling agent and nano-silica sol, so that the adhesion between the coating and the concrete base is ≥5MPa and the water absorption rate is ≤0.5%, which is more than 50% higher than that of traditional epoxy primers.

[0016] In the sealing layer, nano-silica and a staged temperature-controlled stirring process (80°C premixing + 90°C thickening) are introduced. Compared with the conventional sealing layer (without nano-silica), the service life is extended by 50%. In addition, nano-silica and styrene-acrylic emulsion form an interpenetrating network structure, and the porosity of the sealing layer is reduced by more than 50%. When preparing the sealing layer, low-speed premixing + high-speed filler dispersion is adopted to avoid nano-silica agglomeration and ensure that the surface roughness (Ra) of the coating is ≤0.3μm.

[0017] In the polyurea topcoat layer, the added graphene nanosheets can work synergistically with the UV absorber, thereby making the tensile strength of the topcoat ≥25MPa and the light retention rate ≥90% after 2000 hours of UV aging. At the same time, the thermal conductivity of graphene allows heat to diffuse quickly during a fire, and the fire resistance limit is increased to 1.5 hours. DETAILED DESCRIPTION

[0018] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in conjunction with the specific implementation methods of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary persons in the art without creative work should fall within the scope of protection of the present invention.

[0019] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0021] In a first aspect, an embodiment of the present application provides an anti-corrosion and fire-proof integrated coating, comprising a concrete base layer, Also included is a nano silicon coating on the surface of the concrete base; A sealing layer, a sealing coating layer, a reactive active primer layer, and a polyurea topcoat layer are sequentially arranged on the surface of the nano-silicon coating away from the concrete base layer; The nano silicon coating is made of the following raw materials in parts by weight: Nano-silica sol: 70-90 parts; silane coupling agent: 1-2 parts; deionized water: 15-20 parts; dispersant: 0.1-0.5 parts; in the art, the dispersant is one of polycarboxylates and ammonium polyacrylate.

[0022] Among them, the synergistic effect of silane coupling agent and nano-silica sol not only forms physical filling, but also generates stable Si-O-Ca bonds through chemical bonding of silanol groups with calcium hydroxide in concrete. The adhesion test value is increased from 2.5MPa of traditional coatings to ≥5MPa, and the interface peeling mode is changed from "coating-base peeling" to "concrete body destruction", proving that the bond strength exceeds the strength of concrete itself. The micro-nano multi-level structure of the nano-silica coating can absorb freeze-thaw stress, and there is no cracking after 50 freeze-thaw cycles (-20℃-20℃), while traditional epoxy primers crack after 20 cycles. This effect is not mentioned in the prior art.

[0023] The sealing layer is made of the following raw materials in parts by weight: Styrene acrylic emulsion: 55-90 parts; calcium carbonate: 30-40 parts; titanium dioxide: 2-5 parts; talc: 10-15 parts; nano silicon dioxide: 5-10 parts; leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part; the leveling agent is a silicone or acrylate leveling agent; the wetting agent is an acetylene glycol or non-ionic surfactant; the thickener is a hydrophobically modified ethylene oxide polyurethane; the film-forming aid is at least one of dodecyl alcohol ester, propylene glycol phenyl ether or dipropylene glycol methyl ether.

[0024] Among them, nano-silica does not simply fill the pores, but forms a three-dimensional interpenetrating network with the carboxyl group (-COOH) of the styrene-acrylic emulsion through hydrogen bonds. Therefore, as shown by the mercury intrusion method test, the porosity is reduced from 15% of the conventional closed layer to <5%, and the pore size distribution is concentrated (10-50nm).

[0025] The sealing coating layer is made of the following raw materials in parts by weight: Polyurethane: 35 parts; Water: 55-60 parts; Pigment: 9 parts; Film-forming aid: 8 parts; Thickener: 0.7 parts; Bactericide: 0.3 parts; PH regulator: 0.1 parts; Defoamer: 0.2 parts; Bridging agent: 1 part; The defoamer is mineral oil.

[0026] The reactive primer layer is made of the following raw materials in weight fractions: Polyaspartic acid ester resin: 50 parts; water: 30 parts; propylene glycol methyl ether: 10 parts; active diluent: 10 parts; curing agent: 20 parts; leveling agent: 1 part; the curing agent is aliphatic isocyanate.

[0027] The polyurea topcoat layer is made of the following raw materials in parts by weight: Polyaspartic acid ester resin: 50-70 parts; aliphatic isocyanate: 30-40 parts; active diluent: 20-30 parts; ultraviolet absorption aid: 0.5-5 parts; film-forming aid: 10 parts; silicone aid: 5 parts; graphene nanosheets: 0.1-0.5 parts.

[0028] Among them, the graphene nanosheets form a continuous heat-conducting network in the polyurea topcoat, and the heat diffuses rapidly along the surface layer during a fire, delaying the temperature rise of the substrate; at the same time, the graphene sheet blocks the diffusion of oxygen and synergizes with the ultraviolet absorber (for example, the benzotriazole used in this embodiment) to improve the weather resistance. In the polyurea topcoat layer, the added graphene nanosheets can synergize with the ultraviolet absorber to make the topcoat tensile strength ≥25MPa, and the light retention rate ≥90% after 2000 hours of ultraviolet aging. At the same time, the thermal conductivity of graphene allows the heat to diffuse rapidly during a fire, and the fire resistance limit is increased to 1.5 hours. Example 1

[0029] The nano silicon coating is made of the following raw materials in parts by weight: 70 parts of nano silica sol; 1 part of silane coupling agent; 15 parts of deionized water; and 0.1 part of dispersant, which is a polycarboxylate.

[0030] The sealing layer is made of the following raw materials in parts by weight: styrene-acrylic emulsion: 55 parts; calcium carbonate: 30 parts; titanium dioxide: 2 parts; talcum powder: 10 parts; nano-silicon dioxide: 5 parts; leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part, the leveling agent is silicone; the wetting agent is acetylene glycol; the thickener is hydrophobically modified ethylene oxide polyurethane; the film-forming aid is dodecyl alcohol ester.

[0031] The sealed coating layer is made of the following raw materials in parts by weight: polyurethane: 35 parts; water: 55-60 parts; pigment: 9 parts; film-forming aid: 8 parts; thickener: 0.7 parts; bactericide: 0.3 parts; pH regulator: 0.1 parts; defoamer: 0.2 parts; bridging agent: 1 part; the bactericide is benzisothiazolinone; the defoamer is mineral oil; and the bridging agent is γ-glycidyloxypropyltrimethoxysilane.

[0032] The reactive active primer layer is made of the following raw materials in weight fractions: polyaspartic acid ester resin: 50 parts; water: 30 parts; propylene glycol methyl ether: 10 parts; active diluent: 10 parts; curing agent: 20 parts; leveling agent: 1 part; the curing agent is aliphatic isocyanate; the active diluent is allyl glycidyl ether.

[0033] The polyurea topcoat layer is made of the following raw materials in parts by weight: polyaspartic acid ester resin: 50 parts; aliphatic isocyanate: 30 parts; active diluent: 20 parts; ultraviolet absorption auxiliary agent: 0.5 parts; film-forming auxiliary agent: 10 parts; silicone auxiliary agent: 5 parts; graphene nanosheet: 0.1 parts. Example 2

[0034] The nano silicon coating is made of the following raw materials in parts by weight: 80 parts of nano silica sol; 1 part of silane coupling agent; 18 parts of deionized water; and 0.3 parts of dispersant, wherein the dispersant is ammonium polyacrylate.

[0035] The sealing layer is made of the following raw materials in parts by weight: styrene-acrylic emulsion: 70 parts; calcium carbonate: 35 parts; titanium dioxide: 4 parts; talcum powder: 13 parts; nano silicon dioxide: 7 parts; leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part, and the leveling agent is an acrylic leveling agent.

[0036] The sealed coating layer is made of the following raw materials in parts by weight: polyurethane: 35 parts; water: 58 parts; pigment: 9 parts; film-forming aid: 8 parts; thickener: 0.7 parts; bactericide: 0.3 parts; pH regulator: 0.1 parts; defoamer: 0.2 parts; bridging agent: 1 part.

[0037] The reactive active primer layer is made of the following raw materials in weight fractions: polyaspartic acid ester resin: 50 parts; water: 30 parts; propylene glycol methyl ether: 10 parts; active diluent: 10 parts; curing agent: 20 parts; and leveling agent: 1 part.

[0038] The polyurea topcoat layer is made of the following raw materials in parts by weight: polyaspartic acid ester resin: 60 parts; aliphatic isocyanate: 35 parts; active diluent: 25 parts; ultraviolet absorption auxiliary agent: 3 parts; film-forming auxiliary agent: 10 parts; silicone auxiliary agent: 5 parts; graphene nanosheets: 0.1-0.5 parts.

[0039] In this example, components not described are the same as those in Example 1. Example 3

[0040] The nano silicon coating is prepared from the following raw materials in parts by weight: 90 parts of nano silica sol; 2 parts of silane coupling agent; 20 parts of deionized water; and 0.5 parts of dispersant.

[0041] The sealing layer is made of the following raw materials in parts by weight: styrene-acrylic emulsion: 90 parts; calcium carbonate: 40 parts; titanium dioxide: 5 parts; talcum powder: 15 parts; nano-silicon dioxide: 10 parts; leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part, the wetting agent is a non-ionic surfactant; the film-forming aid is dipropylene glycol methyl ether.

[0042] The sealed coating layer is made of the following raw materials in parts by weight: polyurethane: 35 parts; water: 60 parts; pigment: 9 parts; film-forming aid: 8 parts; thickener: 0.7 parts; bactericide: 0.3 parts; pH regulator: 0.1 parts; defoamer: 0.2 parts; bridging agent: 1 part.

[0043] The reactive active primer layer is made of the following raw materials in weight fractions: polyaspartic acid ester resin: 50 parts; water: 30 parts; propylene glycol methyl ether: 10 parts; active diluent: 10 parts; curing agent: 20 parts; and leveling agent: 1 part.

[0044] The polyurea topcoat layer is made of the following raw materials in parts by weight: polyaspartic acid ester resin: 70 parts; aliphatic isocyanate: 40 parts; active diluent: 30 parts; ultraviolet absorption auxiliary agent: 5 parts; film-forming auxiliary agent: 10 parts; silicone auxiliary agent: 5 parts; graphene nanosheet: 0.5 parts.

[0045] In this example, components not described are the same as those in Example 1.

[0046] Comparative Example 1: The nano-silicon coating was removed and a conventional epoxy primer was used, wherein the conventional epoxy primer comprises 50 parts of epoxy resin, 10 parts of curing agent and 40 parts of solvent.

[0047] Comparative Example 2: The nano-silicon coating is retained but the silane coupling agent is removed.

[0048] Comparative Example 3: Nano-silicon dioxide was removed from the sealing layer, and only talcum powder and calcium carbonate were used.

[0049] Comparative Example 4: Graphene is removed from the polyurea topcoat, leaving only the UV absorber.

[0050] Through the experiment, the experimental results are obtained as shown in Table 1. In Table 1, CE1 is represented as Comparative Example 1, CE2 is represented as Comparative Example 2, CE3 is represented as Comparative Example 3, and CE4 is represented as Comparative Example 4.

[0051] Table 1: Performance test table of different ingredients

[0052] What you need to know is that the adhesion test method is GB / T 5210-2006. A special adhesive is used to bond the test column to the coating surface, and the tensile strength (unit: MPa) is measured by a tensile testing machine to measure the adhesion between the coating and the substrate or between the coatings.

[0053] The test method for water absorption is ASTM D570-2022, which involves immersing the sample in 23°C distilled water for 24 hours (or a specific time), calculating the percentage of mass change, and determining the water absorption of the material in a water-immersion or high-humidity environment.

[0054] The test method for salt spray resistance time is ASTM B117-2023. The sample is placed in a 5% NaCl salt spray chamber, and corrosion, blistering, and peeling are regularly observed to evaluate the corrosion resistance of the coating in a salt spray environment.

[0055] The test method for UV aging light retention is QUV-A 2000h-2021 cycle of UV irradiation (60℃) and condensation, with a total duration of 2000 hours, simulating the accelerated aging test of the coating in the UV (UVA-340 lamp) and condensation environment.

[0056] The test method for fire resistance limit is GB / T 9978.1-2019. The sample is placed under a standard fire source, and the time it loses integrity and thermal insulation is recorded to determine the fire resistance limit of the coating.

[0057] The surface roughness test method is GB / T 3505-2020. A stylus profilometer is used to measure the surface profile of the coating and calculate the arithmetic mean deviation (Ra).

[0058] The freeze-thaw cycle test method is ASTM D6944-2020. The sample is immersed and then repeatedly frozen and thawed 50 times. Cracks or peeling are observed to evaluate the coating's anti-cracking performance under freeze-thaw cycles (-20℃~20℃).

[0059] It can be seen from the table above that the adhesion of Example 2 is 5.2 MPa, which is much higher than 2.1 MPa of CE1 and 3.0 MPa of CE2. This is because the silane coupling agent in the nano-silicon coating forms a chemical bond (Si-O-Ca bond) with the concrete, which significantly improves the interface bonding strength.

[0060] The water absorption rate of Example 2 is 0.3%, which is only 1 / 6 of the water absorption rate of CE1 (1.8%), and has an outstanding anti-permeability advantage. This is due to the hydrophobic modification of nano-silica sol and the pore filling effect of nano-silica in the sealing layer; although the water absorption rate of CE4 is the same as that of Example 2, other properties (such as salt spray resistance and fire resistance limit) are still weaker than those of Example 2.

[0061] The salt spray resistance time of Example 2 is 1500 hours, which is the best among the comparative examples and 2.5 times that of CE1. This is because the three-dimensional interpenetrating network structure (nanosilica + styrene acrylic emulsion) of the closed layer effectively blocks the penetration of chloride ions. The salt spray resistance time of CE4 is 1450 hours, which is close to that of Example 2, but the fire resistance limit (1.0h) is lower, indicating that its formula has shortcomings.

[0062] The UV aging gloss retention rate of Example 2 is 90%, which is significantly higher than CE1 (40%) and CE4 (65%). This is because of the synergistic protection of the thermal conductive network of graphene + UV absorber in the polyurea topcoat. Although the gloss retention rates of CE2 (85%) and CE3 (88%) are relatively high, the salt spray resistance and adhesion are insufficient, indicating that their formulas focus on a single performance.

[0063] The fire resistance limit of Example 2 is 1.5 hours, which is much higher than 0.5h of CE1 and 1.0h of CE4. This is because the thermal diffusion of graphene and the high crosslinking density of polyurea topcoat slow down the spread of fire. Although the fire resistance limits of CE2 and CE3 are the same as that of Example 2, other properties (such as water absorption and surface roughness) are weaker.

[0064] The surface roughness of Example 2 is Ra = 0.3 μm, and the coating surface is smoother, which is better than 1.2 μm of CE1 and 0.7 μm of CE3. This is because of the optimized selection of staged temperature control stirring process + leveling agent.

[0065] After 50 freeze-thaw cycles, there was no crack in Example 2, while there was crack in CE1 and microcrack in CE2. This is because the micro-nanostructure of the nano-silicon coating absorbs the freeze-thaw stress and the silane coupling agent enhances the interface toughness. Example 4

[0066] This embodiment also provides a method for preparing a sealing layer, which comprises: Stir styrene acrylic emulsion, leveling agent, wetting agent, film-forming aid and deionized water at 80℃ for 30min at a stirring speed of 250r / min; Then add calcium carbonate, titanium dioxide, talcum powder, and nano-silicon dioxide in stages, and adjust the stirring speed to 500r / min; Add thickener and continue stirring for 10 minutes. When the stirring temperature rises to 90°C and the viscosity reaches 80KU / 25°C, stop stirring. Obtain a closed layer.

[0067] Among them, at a high temperature of 80°C, the dynamic bonds between nano-silica and styrene-acrylic emulsion are reorganized to repair microcracks (SEM observations confirm that cracks can be self-healed when the width is ≤5μm). In the premixing stage at 80°C, the molecular chains of the styrene-acrylic emulsion are fully extended to coat the filler; after heating to 90°C, the thickener and styrene-acrylic emulsion form a "core-shell" structure, the viscosity is precisely controlled (80-90KU), and the coating penetration depth reaches 200μm in the concrete surface, far exceeding the 50μm of conventional processes. The introduction of nano-silica and the staged temperature-controlled mixing process (80°C premixing + 90°C thickening) extends the life of the conventional sealing layer (without nano-silica) by 50%. When preparing the sealing layer, low-speed premixing + high-speed filler dispersion is used to avoid nano-silica agglomeration and ensure that the surface roughness (Ra) of the coating is ≤0.3μm. Example 5

[0068] This embodiment also provides a method for preparing a closed coating layer, which comprises: Polyurethane, water, pigment, film-forming aid, thickener, bactericide, pH regulator, defoamer, and bridging agent are mixed in a high-speed disperser at 40-50°C, with a stirring speed of 1000r / min, and stirred for 20 minutes until the viscosity reaches 150KU / 25°C, to obtain a uniform closed coating dispersion with a fineness of less than 50μm; Obtain a closed coating layer. Example 6

[0069] This embodiment also provides a method for preparing a reactive active primer layer, which comprises: Disperse polyaspartic acid ester resin, water, propylene glycol methyl ether, active diluent, curing agent and leveling agent at 40°C and stirring speed of 800r / min for 30min, add thickener and continue stirring for 10min, stop stirring when the viscosity reaches 5Ku; A reactive active primer layer is obtained. Example 7

[0070] This embodiment also provides a method for preparing a polyurea topcoat layer, which comprises: Add the active diluent into the high-speed disperser, slowly add the graphene nanosheets, start the high-speed disperser at the same time, set the stirring speed to 1500r / min, and continue dispersing for 45 minutes to form a pre-dispersed mixed solution; The pre-dispersed mixed solution was transferred to the container of a vacuum mixer, and then polyaspartic acid ester resin was added, and the stirring speed was set to 400 r / min; During the stirring process, slowly add the UV absorbing agent, film-forming agent and silicone agent, and set the stirring time to 15 minutes; Then add aliphatic isocyanate, set the stirring speed to 1000r / min, and stir for 15min; Add thickener and continue stirring for 103 minutes. When the viscosity reaches 80KU / 25℃, stop stirring. A polyurea topcoat layer was obtained.

[0071] The graphene nanosheets are pre-dispersed in an active diluent (eg, glycidyl ether used in this embodiment), and the polar groups of the active diluent are used to adsorb the graphene nanosheets to avoid agglomeration (transmission electron microscopy shows that the interlamellar spacing is stable at 0.8-1.2 nm). Example 8

[0072] This embodiment also provides a method for preparing an anti-corrosion and fire-proof integrated coating, comprising the following steps: Clean the surface of the concrete base away from the wall: Apply a layer of nano silicon coating on the surface of the concrete base; A sealing layer is set on the surface of the nano-silicon coating: a latex paint of the sealing layer is applied on the surface of the nano-silicon coating through a coating roller, and the speed of the coating roller is controlled at 20N / MIN; Set a sealed coating layer on the surface of the sealing layer: use a coating roller to apply it on the surface of the sealing layer, and the speed of the coating roller is 20N / MIN; A reactive active primer layer is provided on the surface of the sealed coating layer: a reactive active primer layer is applied on the surface of the sealed coating layer through a coating roller, and the rotation speed of the coating roller is controlled at 20N / MIN; A polyurea topcoat layer is provided on the surface of the reactive active primer layer: the polyurea topcoat layer is applied on the surface of the reactive active primer layer through a coating roller, and the rotation speed of the coating roller is controlled at 20N / MIN; The coated coating is placed at a temperature of 70°C and a humidity of 70RH%. It should be noted that under the conditions of 70°C / 70%RH, the water evaporation rate of the nano-silicon coating reaches a balance with the condensation reaction rate to avoid the generation of microcracks. The reaction is carried out for 16 hours and then at a temperature of 30°C and a humidity of 70RH% for 12 hours to form an integrated coating.

[0073] At a coating speed of 20 N / min, the coating of the sealing layer (viscosity 80-90 KU) achieves 100% filling of the pores of the nano-silicon coating.

[0074] Compared with some existing preparation methods, in this embodiment: when the coating speed is greater than 30N / min, the sealing layer causes the filler to settle due to excessive shearing, and the porosity rebounds to 10%; when the coating speed is less than 15N / min, the coating thickness is uneven (fluctuation ±10μm).

[0075] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. An anticorrosion and fireproof integrated coating, comprising a concrete base, characterized in that: Also included is a nano silicon coating on the surface of the concrete base; A sealing layer, a sealing coating layer, a reactive active primer layer, and a polyurea topcoat layer are sequentially arranged on the surface of the nano-silicon coating away from the concrete base layer; The nano silicon coating is made of the following raw materials in parts by weight: Nano silica sol: 70-90 parts; Silane coupling agent: 1-2 parts; Deionized water: 15-20 parts; Dispersant: 0.1-0.5 parts.

2. The anticorrosion and fireproofing integrated coating according to claim 1, characterized in that: The sealing layer is made of the following raw materials in parts by weight: Styrene acrylic emulsion: 55-90 parts; calcium carbonate: 30-40 parts; titanium dioxide: 2-5 parts; talc: 10-15 parts; nano silicon dioxide: 5-10 parts; Leveling agent: 0.7 parts; wetting agent: 0.8 parts; film-forming aid: 6 parts; deionized water: 30 parts; thickener: 1 part.

3. The anticorrosion and fireproofing integrated coating according to claim 2, characterized in that: The sealed coating layer is made of the following raw materials in parts by weight: Polyurethane: 35 parts; Water: 55-60 parts; Pigment: 9 parts; Film-forming aid: 8 parts; Thickener: 0.7 parts; Bactericide: 0.3 parts; PH regulator: 0.1 parts; Defoaming agent: 0.2 parts; Bridging agent: 1 part.

4. The anticorrosion and fireproofing integrated coating according to claim 3, characterized in that: The reactive active primer layer is made of the following raw materials in weight fraction: Polyaspartic acid ester resin: 50 parts; Water: 30 parts; Propylene glycol methyl ether: 10 parts; Active diluent: 10 parts; Curing agent: 20 parts; Leveling agent: 1 part.

5. The anticorrosion and fireproofing integrated coating according to claim 4, characterized in that: The polyurea topcoat layer is made of the following raw materials in parts by weight: Polyaspartic acid ester resin: 50-70 parts; aliphatic isocyanate: 30-40 parts; reactive diluent: 20-30 parts; ultraviolet absorption aid: 0.5-5 parts; Film-forming agent: 10 parts; silicone additive: 5 parts; graphene nanosheets: 0.1-0.5 parts.

6. The anticorrosion and fireproofing integrated coating according to claim 5, characterized in that: The preparation method of the sealing layer comprises: Stir styrene acrylic emulsion, leveling agent, wetting agent, film-forming aid and deionized water at 80°C for 30-45 minutes at a stirring speed of 250-300 r / min; Then add calcium carbonate, titanium dioxide, talcum powder, and nano silicon dioxide in stages, and adjust the stirring speed to 500-600r / min; Add thickener and continue stirring for 10-15 minutes. When the stirring temperature rises to 90°C and the viscosity reaches 80-90KU / 25°C, stop stirring. Obtain a closed layer.

7. The anticorrosion and fireproofing integrated coating according to claim 6, characterized in that: The method for preparing the closed coating layer comprises: Polyurethane, water, pigment, film-forming aid, thickener, bactericide, pH regulator, defoamer, and bridging agent are mixed in a high-speed disperser at 40-50°C, with a stirring speed of 1000-1200 r / min, for 20-40 minutes, and the viscosity reaches 150±20KU / 25°C, to obtain a uniform closed coating dispersion with a fineness of less than 50μm; Obtain a closed coating layer.

8. The anticorrosion and fireproofing integrated coating according to claim 7, characterized in that: The method for preparing the reactive active primer layer comprises: Disperse polyaspartic acid ester resin, water, propylene glycol methyl ether, active diluent, curing agent and leveling agent at 40-50°C and stirring speed of 800-1000r / min for 30-45min, add thickener and continue stirring for 10-15min, stop stirring when the viscosity reaches 5-10Ku; A reactive active primer layer is obtained.

9. The anticorrosion and fireproofing integrated coating according to claim 8, characterized in that: The preparation method of the polyurea topcoat layer comprises: Add the active diluent to the high-speed disperser, slowly add the graphene nanosheets, start the high-speed disperser at the same time, set the stirring speed to 1000-2000r / min, and continue dispersing for 30-60min to form a pre-dispersed mixed solution; Transfer the pre-dispersed mixed liquid to the container of a vacuum mixer, then add the polyaspartic acid ester resin and set the stirring speed to 300-500r / min; During the stirring process, slowly add the UV absorbing agent, film-forming agent and silicone agent, and set the stirring time to 10-15 minutes; Then add aliphatic isocyanate, set the stirring speed to 800-1200r / min, and stir for 10-15min; Add thickener and continue stirring for 10-15 minutes. When the viscosity reaches 70-90KU / 25℃, stop stirring. A polyurea topcoat layer was obtained.

10. A method for preparing an anticorrosion and fireproof integrated coating, characterized in that: The method is used to prepare the anti-corrosion and fire-proof integrated coating according to any one of claims 1 to 9, and the method for preparing the anti-corrosion and fire-proof integrated coating also includes the following steps: Clean the surface of the concrete base away from the wall: Apply a layer of nano silicon coating on the surface of the concrete base; A sealing layer is provided on the surface of the nano-silicon coating: a latex paint of the sealing layer is applied on the surface of the nano-silicon coating through a coating roller, and the speed of the coating roller is controlled at 20-30 N / MIN; Set a sealed coating layer on the surface of the sealing layer: use a coating roller to apply it on the surface of the sealing layer, and the speed of the coating roller is 20-25N / MIN; A reactive active primer layer is provided on the surface of the sealed coating layer: a reactive active primer layer is applied on the surface of the sealed coating layer through a coating roller, and the rotation speed of the coating roller is controlled at 20 to 30 N / MIN; A polyurea topcoat layer is provided on the surface of the reactive active primer layer: the polyurea topcoat layer is applied on the surface of the reactive active primer layer through a coating roller, and the rotation speed of the coating roller is controlled at 20 to 30 N / MIN; The coated coating is reacted at a temperature of 70-85°C and a humidity of 70-85RH% for 16-24 hours, and then at a temperature of 30-35°C and a humidity of 70-85RH% for 12-18 hours to form an integrated coating.

Citation Information

Patent Citations

  • Graphene powder metallic topcoat and preparation method thereof

    CN109354978A

  • Concrete surface permeation consolidation type self-repairing coating and preparation method thereof

    CN110818448A

  • Cement concrete surface coating structure with acid-resistant and corrosion-resistant functions

    CN119684866A

  • Method for coating concrete face

    JP2008088018A

  • Silane-modified elastic urea resin-based waterproofing / anticorrosion material containing ceramic metal with enhanced wet-surface adhesion performance and durability using tetraethoxy silane compound as solvent, and waterproofing / anticorrosion method using same

    KR101371345B1